2021
DOI: 10.1002/jcla.23706
|View full text |Cite
|
Sign up to set email alerts
|

GC‐MS metabolomics identifies novel biomarkers to distinguish tuberculosis pleural effusion from malignant pleural effusion

Abstract: Pleural effusions (PEs) arise from a variety of systemic, inflammatory, infectious, and malignant conditions. 1 When a pleural effusion is considered, efforts should be made to find the cause of the effusion to ensure the appropriate treatment therapy. Pleural effusions may be classified into transudates or exudates based on the mechanism of fluid formation. If the patient has a transudative effusion, the systemic abnormality can be treated and no attention needs to be diverted to the pleura. Alternatively, if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Also, other tumor markers have been reported to be useful in lung cancer (such as CYFRA 21-1, NSE, or CR), which were not evaluated in this study. In addition, novel biomarkers, such as serum interleukin-27 (IL-27), gas chromatography-mass spectrometry (GC-MS) metabolomics, and serum reactive oxygen species modulator 1 (ROMO1), have been proposed as potential indexes for diagnosing lung cancer-associated MPE, but only a few were routinely detected in clinical practice (18,(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Also, other tumor markers have been reported to be useful in lung cancer (such as CYFRA 21-1, NSE, or CR), which were not evaluated in this study. In addition, novel biomarkers, such as serum interleukin-27 (IL-27), gas chromatography-mass spectrometry (GC-MS) metabolomics, and serum reactive oxygen species modulator 1 (ROMO1), have been proposed as potential indexes for diagnosing lung cancer-associated MPE, but only a few were routinely detected in clinical practice (18,(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis was performed using a well-established previously published statistical method [ 59 , 60 ]. Following the acquisition of the raw data, these data are aligned with the aid of Compound Discover using the 3.0 system from Thermo based on their m/z ratio and the retention times of ion signals.…”
Section: Methodsmentioning
confidence: 99%
“…The result indicated more activation of the downstream kynurenine metabolism. A recent non-targeted metabolomics study ( Liu et al, 2021 ) with relatively small cohorts of TPE (n = 17) and MPE (n = 17) patients found that stearic acid, L-cystine, and citric acid may be potential biomarkers for distinguishing between TBPE and MPE, with decent sensitivity and specificity. The OPLS-DA resulted in a fairly low Q 2 = 0.30, possibly due to the small sample size.…”
Section: Biomarkers Based On Host Responsesmentioning
confidence: 99%